2018
DOI: 10.1038/s41598-018-26113-0
|View full text |Cite
|
Sign up to set email alerts
|

Enabling STD-NMR fragment screening using stabilized native GPCR: A case study of adenosine receptor

Abstract: Structural studies of integral membrane proteins have been limited by the intrinsic conformational flexibility and the need to stabilize the proteins in solution. Stabilization by mutagenesis was very successful for structural biology of G protein-coupled receptors (GPCRs). However, it requires heavy protein engineering and may introduce structural deviations. Here we describe the use of specific calixarenes-based detergents for native GPCR stabilization. Wild type, full length human adenosine A2A receptor was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 76 publications
5
53
0
Order By: Relevance
“…A 2A R shows a smear signal. This is consistent with the presence of different non‐aggregated oligomers as recently reported . Native PAGE and SEC confirmed that AcrB, BmrA and A 2A R were not aggregated when DDM/CALX‐173‐GK were used for both solubilization and purification ( 5B ).…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…A 2A R shows a smear signal. This is consistent with the presence of different non‐aggregated oligomers as recently reported . Native PAGE and SEC confirmed that AcrB, BmrA and A 2A R were not aggregated when DDM/CALX‐173‐GK were used for both solubilization and purification ( 5B ).…”
Section: Figuresupporting
confidence: 91%
“…We then investigated the function of each solubilized and purified membrane protein. We compared CALX‐173‐GK condition to a reference as previously reported, (DDM for BmrA and AcrB, DDM/CHS for A 2A R). Very similar ligand binding activity was observed for AcrB in both solubilization and purification conditions.…”
Section: Figurementioning
confidence: 99%
“…Solubilization of A 2A R and AcrB: Adenosine receptor (A 2A R) was expressed in insect cells as described . AcrB was expressed in E.coli as previously reported .…”
Section: Methodsmentioning
confidence: 99%
“…It was proposed and partially proved that these amphiphiles freeze the monomeric structure of the protein, preventing its aggregation and denaturation, through hydrophobic interactions with the protein membrane region and through a network of salt bridges with the basic residues at the cytosol-membrane interface. With the aim of overcoming what has been indicated as a bottleneck in the membrane protein structural biology, [75] in the latest years other studies appeared where the stabilisation, isolation and characterisation of membrane proteins such as Human Multidrug Resistance Protein 4 [76] and G protein-coupled receptors, [77] using similar calixarene detergents, were reported. A glycocalixarene having glucose units at the upper and an heptyl chain at the lower rim also showed to preserve and stabilise, even over long periods of time, the function of three native membrane proteins.…”
Section: Calixarene-based Detergents For Membrane Proteinsmentioning
confidence: 99%